Flame-retardant wear-resistant fabric and preparation method thereof
By adopting a multi-layer structure in flame retardant fabrics, combined with the use of melt polycondensation method and nanographene, the problem of insufficient wear resistance and long-term flame retardant performance of existing flame retardant fabrics is solved, and efficient and durable flame retardant and wear-resistant fabrics are achieved.
Patent Information
- Application Number
- CN202510000136.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-18
AI Technical Summary
The flame retardant fabrics have reduced flame retardant effects after washing and friction, and have insufficient wear resistance, short service life and high cost.
A multi-layer fabric structure including a skin layer, a flame retardant layer and a surface layer is adopted. The skin layer is pure cotton fabric. The flame retardant layer is prepared by melt condensation and polycondensation method, nanographene is added to improve wear resistance, and water-based acrylate resin and other materials are coated on the surface to enhance waterproofing and wear resistance.
It achieves long-term flame retardant performance and good wear resistance, extends the service life of the fabric, reduces costs, and improves the waterproof effect of the fabric.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabrics, in particular to a flame retardant and wear-resistant fabric and a preparation method thereof. Background Art
[0002] The present invention relates to that with the improvement of living standards and safety awareness, people are no longer satisfied with the comfort performance of fabrics, but have higher demands for textile fabrics with protective functions. Among them, flame-retardant fabrics have been widely developed and are widely used in industries such as petrochemicals, electric power, fire protection, coal mining, and oil refining. Most flame-retardant fabrics on the market are treated with flame retardant methods such as dipping, coating, and organic solvents. Most of the finished fabrics have certain toxicity and are not washable. With the increase in the number of washings after wearing, the flame retardant effect is mostly getting worse. In daily life, the clothes people wear are constantly rubbed, and they are prone to wear and deformation after long-term use. The cost of flame-retardant fabrics is higher than that of ordinary fabrics. Improving their wear resistance can extend their service life and save costs. Summary of the invention
[0003] The purpose of the present invention is to provide a flame retardant and wear resistant fabric and a preparation method thereof, so as to solve the problems existing in the prior art.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a flame retardant and wear-resistant fabric, comprising a skin-contacting layer, a flame retardant layer, and a surface layer, wherein the skin-contacting layer has a gram weight of 100-120 g / m 2 The pure cotton fabric has the following components in parts by weight: 40-80 parts of water-based acrylate; 5-25 parts of solvent; 15-25 parts of nano silica sol; 1~5 parts of coupling agent; Nano aluminum hydroxide 5-10 parts; 3-4 parts of polytetrafluoroethylene nanopowder; 1~10 parts of photoinitiator; 0.3~1 part of ethylene bisoleamide.
[0005] 2. A flame-retardant and wear-resistant fabric according to claim 1, characterized in that the polyester fabric is prepared by mixing polyester and graphene with a particle size of 10-50 nm in a high-speed mixer at a mass ratio of 100:1-15, melt spinning to obtain fibers at a melt spinning temperature of 220-250°C, and then weaving to obtain fibers with a gram weight of 100-120 g / m 2 .
[0006] 3. A flame-retardant and wear-resistant fabric according to claim 2, characterized in that the polyester is prepared by melt polycondensation of phosphorus-containing diacid, sulfonic acid diol, and 1-(3-aminophenyl)ethane-1,2-diol under the action of a catalyst, and the specific preparation method is: adding the sulfonic acid diol, the phosphorus-containing diacid, and the catalyst into an esterification reactor for a first esterification reaction, the pressure of the first esterification reaction is 0.1~0.5MPa, the reaction temperature is 200~230℃, and the reaction time is 2~6h, adding 1-(3-aminophenyl)ethane-1,2-diol, the reaction pressure is 0.1~0.5Mpa, the reaction temperature is 210~250℃, the reaction time is 0.5~3h, and then polycondensation is performed at 225~240℃ for 2~4h.
[0007] 4. A flame-retardant and wear-resistant fabric according to claim 3, characterized in that the molar ratio of the phosphorus-containing diacid, sulfonic acid diol, and 1-(3-aminophenyl)ethane-1,2-diol is 1.0~1.2:1:0.1~0.5.
[0008] 5. A flame-retardant and wear-resistant fabric according to claim 3, characterized in that the phosphorus-containing diacid is phosphobutyl succinic acid, and the sulfonic diol is at least one of 2,3-dihydroxypropane-1-sulfonic acid, 1,3-dihydroxyprop-2-yl-4-methylbenzenesulfonate, 1,5-dihydroxypentane-1,5-disulfonic acid disodium, and 1,4-dihydroxy-2-butane sodium sulfonate.
[0009] 6. The flame-retardant and wear-resistant fabric according to claim 3, characterized in that the catalyst is a titanium catalyst or an antimony catalyst, accounting for 0.5-3.5% of the mass of the sulfonic acid diol.
[0010] 7. The flame-retardant and wear-resistant fabric according to claim 1, characterized in that the water-based acrylic resin is selected as 6014 water-based acrylic resin produced by Runchang Chemical.
[0011] 8. The flame-retardant and wear-resistant fabric according to claim 1, characterized in that the solvent is a 50wt% ethanol aqueous solution.
[0012] 9. The flame-retardant and wear-resistant fabric according to claim 1, characterized in that the coupling agent is at least one of KH171, KH151, and ethylene tris[(1-methylvinyl)oxy]silane.
[0013] Compared with the prior art, the beneficial effects achieved by the present invention are: (1) The preparation method involved in the present invention is simple in process and easy to implement. Through the melt polycondensation method, the present invention uses phosphorus-containing diacid and sulfonic acid diol as raw materials and 1-(3-aminophenyl)ethane-1,2-diol as a modifier to obtain polyester fiber, whose molecular chain contains multiple elements of P, S, and N. Phosphoric acid and sulfonic acid groups promote the decomposition of polyester and surface coating during thermal decomposition to form an expanded carbon layer, which effectively protects the skin-contacting fabric. At the same time, the released nitrogen-containing gas dilutes the combustion environment, effectively reduces the combustion heat, and makes the fabric quickly self-extinguish, forming a flame retardant synergistic effect and improving the flame retardant effect. The present invention introduces flame retardant elements into the fiber polymer molecular chain. Compared with traditional external additives, there will be no migration phenomenon, so it has good long-term flame retardancy. In addition, due to the presence of phenyl in 1-(3-aminophenyl)ethane-1,2-diol, it is easier to form carbon during combustion, thereby improving the flame retardant effect; (2) In the process of melt polycondensation, the present invention adds nanographene as a filler. Nanographene has excellent wear resistance, can effectively improve the wear resistance of the fabric, and can also enhance the fluidity of the polymer matrix, improve the processing performance of the composite material, and make it perform more smoothly during the processing; (3) The coating prepared by acrylic resin in the present invention is applied on the surface of flame-retardant fabric. Acrylic resin has good film-forming property and contains multiple active sites, which can be combined with flame-retardant fabric by hydrogen bonding, so that it has good adhesion performance on the surface of fabric, high strength and good wear resistance. Under the action of double-bond coupling agent, nano-silica gel participates in the polymerization of polyacrylic resin, initiates cross-linking reaction, improves compatibility, introduces organic silane chain segments, and changes the surface coating from hydrophilic to hydrophobic, thereby improving the waterproof effect of fabric, and can also improve the wear resistance and flame retardant effect of fabric. The appropriate amount of nano-aluminum hydroxide, polytetrafluoroethylene nano-powder and ethylene bisoleamide are added to cooperate with each other to play a good synergistic role, are evenly dispersed in the raw material system of the present invention, have good lubricating and dispersing effect, and improve wear resistance. DETAILED DESCRIPTION
[0014] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Example 1
[0015] (1) Add 2,3-dihydroxypropane-1-sulfonic acid, phospho-succinic acid and titanium catalyst into an esterification reaction kettle for a first esterification reaction, wherein the pressure of the first esterification reaction is 0.1 MPa, the reaction temperature is 200°C and the reaction time is 4 hours, and then add 1-(3-aminophenyl)ethane-1,2-diol, the reaction pressure is 0.1 MPa, the reaction temperature is 210°C and the reaction time is 2.5 hours, and then polycondense at 225°C for 4 hours to obtain polyester; the molar ratio of the phosphorus-containing diacid, sulfonic acid diol and 1-(3-aminophenyl)ethane-1,2-diol is 1.0:1:0.1, and the titanium catalyst accounts for 1.5% of the mass of the sulfonic acid diol; (2) Polyester and graphene with a particle size of 10 nm are mixed in a high-speed mixer at a mass ratio of 100:1, and melt-spun to obtain fibers at a melt-spinning temperature of 220-250°C. The fibers are then woven to obtain fibers with a gram weight of 100 g / m 2 Flame retardant fabric; (3) 100g / m 2 The pure cotton fabric is used as the skin-friendly layer fabric, and the flame-retardant layer fabric is connected together by double-layer bonding; (4) adding tetraethyl orthosilicate slowly dropwise to dilute nitric acid with a concentration of 0.1 mol / L at a rate of 500 μL / mL at 48°C for hydrolysis, and stirring at a constant temperature for 5 hours to obtain nano-silica sol, wherein the ratio of tetraethyl orthosilicate to dilute nitric acid is 100 g:150 mL; (5) 15 parts by weight of nano silica gel and 1 part by weight of coupling agent were stirred at 38°C and 200 rpm for 1 hour, then the speed was increased to 450 rpm, 40 parts by weight of aqueous acrylate and 5 parts by weight of 50 wt% ethanol aqueous solution were added, and the mixture was stirred for 1 hour. The speed was reduced to 200 rpm, and 5 parts by weight of nano aluminum hydroxide, 3 parts by weight of polytetrafluoroethylene nano powder with a particle size of 200 nm, 0.3 parts by weight of ethylene bisoleamide, and 1 part by weight of photoinitiator were added, and the mixture was stirred for 30 minutes to obtain a surface coating; (6) Apply the surface coating to a layer of flame retardant fabric, place it in a kneading machine for kneading after the coating is cured, and repeat the coating, curing and kneading operations three times. The first coating thickness is 15nm, and the second and third coating thicknesses decrease by 5nm respectively. The curing is: baking at 90℃ for 10min, and then UV light curing for 30min; after curing, the kneading speed is 60r / min, and the kneading time is 4min, to obtain a flame retardant and wear-resistant fabric. Example 2
[0016] (1) Adding 1,3-dihydroxypropane-2-yl-4-methylbenzenesulfonate, phosphobutyl succinic acid and a titanium catalyst into an esterification reaction kettle for a first esterification reaction, wherein the pressure of the first esterification reaction is 0.2 MPa, the reaction temperature is 210°C and the reaction time is 4 hours, adding 1-(3-aminophenyl)ethane-1,2-diol, the reaction pressure is 0.2 MPa, the reaction temperature is 215°C and the reaction time is 2 hours, and then polycondensing at 230°C for 3 hours to obtain polyester; the molar ratio of the phosphorus diacid, sulfonic acid diol and 1-(3-aminophenyl)ethane-1,2-diol is 1.0:1:0.2, and the titanium catalyst accounts for 2.5% of the mass of the sulfonic acid diol; (2) Polyester and graphene with a particle size of 20 nm were mixed in a high-speed mixer at a mass ratio of 100:5, and melt-spun to obtain fibers at a melt spinning temperature of 220-250°C. The fibers were then woven to obtain fibers with a gram weight of 100 g / m 2 Flame retardant fabric; (3) 100g / m 2 The pure cotton fabric is used as the skin-friendly layer fabric, and the flame-retardant layer fabric is connected together by double-layer bonding; (4) adding tetraethyl orthosilicate slowly dropwise to dilute nitric acid with a concentration of 0.1 mol / L at a rate of 500 μL / min at 50°C for hydrolysis, and stirring at a constant temperature for 6 hours to obtain nano-silica sol, wherein the ratio of tetraethyl orthosilicate to dilute nitric acid is 100 g:150 mL; (5) 18 parts by weight of nano silica gel and 2 parts by weight of coupling agent were stirred at 39°C and 250 rpm for 1 hour, then the speed was increased to 480 rpm, 50 parts by weight of aqueous acrylate and 10 parts by weight of 50 wt% ethanol aqueous solution were added, and the mixture was stirred for 2 hours. The speed was reduced to 200 rpm, and 6 parts by weight of nano aluminum hydroxide, 3.5 parts by weight of polytetrafluoroethylene nano powder with a particle size of 300 nm, 0.6 parts by weight of ethylene bisoleamide, and 2 parts by weight of photoinitiator were added, and the mixture was stirred for 30 minutes to obtain a surface coating; (6) Apply the surface coating to a layer of flame retardant fabric, place it in a kneading machine for kneading after the coating is cured, and repeat the coating, curing and kneading operations three times. The first coating thickness is 16nm, and the second and third coating thicknesses decrease by 5nm respectively. The curing is: baking at 90℃ for 10min, and then UV light curing for 30min; after curing, the kneading speed is 60r / min, and the kneading time is 4min, to obtain a flame retardant and wear-resistant fabric. Example 3
[0017] (1) Adding disodium 1,5-dihydroxypentane-1,5-disulfonic acid, phospho-succinic acid and antimony catalyst into an esterification reaction kettle for a first esterification reaction, wherein the pressure of the first esterification reaction is 0.3 MPa, the reaction temperature is 220°C and the reaction time is 3 hours, adding 1-(3-aminophenyl)ethane-1,2-diol, the reaction pressure is 0.3 MPa, the reaction temperature is 230°C and the reaction time is 1.5 hours, and then polycondensing at 235°C for 2.5 hours to obtain polyester; the molar ratio of the phosphorus-containing diacid, sulfonic acid diol and 1-(3-aminophenyl)ethane-1,2-diol is 1.1:1:0.3, and the antimony catalyst accounts for 2.5% of the mass of the sulfonic acid diol; (2) Polyester and graphene with a particle size of 30 nm were mixed in a high-speed mixer at a mass ratio of 100:8, and melt-spun to obtain fibers at a melt-spinning temperature of 220-250°C. The fibers were then woven to obtain fibers with a gram weight of 110 g / m 2 Flame retardant fabric; (3) 110g / m 2 The pure cotton fabric is used as the skin-friendly layer fabric, and the flame-retardant layer fabric is connected together by double-layer bonding; (4) adding tetraethyl orthosilicate slowly dropwise to dilute nitric acid with a concentration of 0.1 mol / L at a rate of 700 μL / min at 50°C for hydrolysis, and stirring at a constant temperature for 6 hours to obtain nano-silica sol, wherein the ratio of tetraethyl orthosilicate to dilute nitric acid is 100 g:150 mL; (5) 20 parts by weight of nano silica gel and 3 parts by weight of coupling agent were stirred at 40°C and 300 rpm for 2 h, then the speed was increased to 500 rpm, 60 parts by weight of aqueous acrylate and 15 parts by weight of 50 wt% ethanol aqueous solution were added, and the mixture was stirred for 2 h. The speed was reduced to 250 rpm, and 8 parts by weight of nano aluminum hydroxide, 4 parts by weight of polytetrafluoroethylene nano powder with a particle size of 300 nm, 0.6 parts by weight of ethylene bisoleamide, and 7 parts by weight of photoinitiator were added, and the mixture was stirred for 30 min to obtain a surface coating; (6) Apply the surface coating to a layer of flame retardant fabric, place it in a kneading machine for kneading after the coating is cured, and repeat the coating, curing and kneading operations three times. The first coating thickness is 18nm, and the second and third coating thicknesses decrease by 5nm respectively. The curing is: baking at 90℃ for 10min, and then UV light curing for 30min; after curing, the kneading speed is 70r / min, and the kneading time is 5min, to obtain a flame retardant and wear-resistant fabric. Example 4
[0018] (1) Sodium 1,4-dihydroxy-2-butanesulfonate, phospho-succinic acid and antimony catalyst are added to an esterification reaction kettle for a first esterification reaction. The pressure of the first esterification reaction is 0.5 MPa, the reaction temperature is 230°C and the reaction time is 6 hours. 1-(3-aminophenyl)ethane-1,2-diol is added. The reaction pressure is 0.5 MPa, the reaction temperature is 250°C and the reaction time is 3 hours. Polycondensation is then carried out at 240°C for 2 hours to obtain polyester. The molar ratio of the phosphorus-containing diacid, sulfonic acid diol and 1-(3-aminophenyl)ethane-1,2-diol is 1.2:1:0.5. The antimony catalyst accounts for 2.5% of the mass of the sulfonic acid diol. (2) Polyester and graphene with a particle size of 30 nm were mixed in a high-speed mixer at a mass ratio of 100:15, and melt-spun to obtain fibers at a melt spinning temperature of 220-250°C. The fibers were then woven to obtain fibers with a gram weight of 120 g / m 2 Flame retardant fabric; (3) 120g / m 2 The pure cotton fabric is used as the skin-friendly layer fabric, and the flame-retardant layer fabric is connected together by double-layer bonding; (4) adding tetraethyl orthosilicate slowly dropwise to dilute nitric acid with a concentration of 0.1 mol / L at a rate of 1000 μL / min at 52°C for hydrolysis, and stirring at a constant temperature for 7 hours to obtain nano-silica sol, wherein the ratio of tetraethyl orthosilicate to dilute nitric acid is 100 g:200 mL; (5) 25 parts by weight of nano silica gel and 5 parts by weight of coupling agent were stirred at 45°C and 300 rpm for 3 h, then the speed was increased to 550 rpm, 80 parts by weight of aqueous acrylate and 25 parts by weight of 50 wt% ethanol aqueous solution were added, and the mixture was stirred for 3 h, then the speed was reduced to 300 rpm, 10 parts by weight of nano aluminum hydroxide, 4 parts by weight of polytetrafluoroethylene nano powder with a particle size of 400 nm, 1 part by weight of ethylene bisoleamide, and 6 parts by weight of photoinitiator were added, and the mixture was stirred for 30 min to obtain a surface coating; (6) Apply the surface coating to a layer of flame retardant fabric, place it in a kneading machine for kneading after the coating is cured, and repeat the coating, curing and kneading operations three times. The first coating thickness is 20nm, and the second and third coating thicknesses decrease by 5nm respectively. The curing is: baking at 90℃ for 10min, and then UV light curing for 30min; after curing, the kneading speed is 80r / min, and the kneading time is 6min, to obtain a flame retardant and wear-resistant fabric.
[0019] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that succinic acid is used instead of phosphorus-containing diacid, and the remaining steps are the same as Example 1.
[0020] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that butanediol is used instead of sulfonic acid diol, and the remaining steps are the same as Example 1.
[0021] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that graphene is not added, and the remaining steps are the same as Example 1.
[0022] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that conventional polyester chips are used instead of the polyester in the present invention, and the remaining steps are the same as those in Example 1.
[0023] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that conventional polyester chips are used instead of the polyester in the present invention, and the polyester chips are mixed with a phosphorus flame retardant and graphene with a particle size of 10 nm in a high-speed mixer at a mass ratio of 100:1:1, and melt-spun to obtain fibers at a melt spinning temperature of 220-250°C, and then woven to obtain fibers with a gram weight of 100 g / m 2 The remaining steps are the same as those in Example 1.
[0024] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that no coupling agent is added, and the remaining steps are the same as Example 1.
[0025] Comparative Example 7 The difference between Comparative Example 7 and Example 1 is that no nano-silica sol is added, and the remaining steps are the same as Example 1.
[0026] Comparative Example 8 The difference between Comparative Example 8 and Example 1 is that no nano aluminum hydroxide is added, and the remaining steps are the same as Example 1.
[0027] Comparative Example 9 The difference between Comparative Example 9 and Example 1 is that no polytetrafluoroethylene nanopowder is added, and the remaining steps are the same as Example 1.
[0028] Comparative Example 10 The difference between Comparative Example 10 and Example 1 is that ethylene bisoleamide is not added, and the remaining steps are the same as Example 1.
[0029] Effect example The flame retardant performance analysis results of Examples 1 to 4 of the present invention and Comparative Examples 1 to 10 are given in Table 1 below, and the wear resistance analysis results of Examples 1 to 4 of the present invention and Comparative Examples 1 to 10 are given in Table 2 below.
[0030] Table 1 Analysis of flame retardant properties of Examples 1 to 4 and Comparative Examples 1 to 10
[0031] Table 2 Analysis of wear resistance of Examples 1 to 5 and Comparative Examples 1 to 10
[0032] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A flame retardant and wear-resistant fabric, comprising a skin-contacting layer, a flame retardant layer, and a surface layer, characterized in that: The skin-contacting layer is made of pure cotton fabric, the flame-retardant layer is made of polyester fabric, and the surface layer includes the following components in parts by weight: 40-80 parts of water-based acrylate; 5-25 parts of solvent; 15-25 parts of nano silica sol; 1~5 parts of coupling agent; Nano aluminum hydroxide 5-10 parts; 3-4 parts of polytetrafluoroethylene nanopowder; 1~10 parts of photoinitiator; 0.3~1 part of ethylene bisoleamide.
2. The flame retardant and wear resistant fabric according to claim 1, characterized in that: The polyester fabric is prepared by mixing polyester and graphene with a particle size of 10-50 nm in a high-speed mixer at a mass ratio of 100:1-15, melt-spinning to obtain fibers, and then weaving.
3. The flame retardant and wear resistant fabric according to claim 2, characterized in that: The polyester is prepared by melt polycondensation of phosphorus diacid, sulfonic acid diol and 1-(3-aminophenyl)ethane-1,2-diol under the action of a catalyst.
4. The flame retardant and wear resistant fabric according to claim 3, characterized in that: The molar ratio of the phosphorus-containing diacid, the sulfonic acid diol, and 1-(3-aminophenyl)ethane-1,2-diol is 1.0-1.2:1:0.1-0.
5.
5. The flame retardant and wear resistant fabric according to claim 3, characterized in that: The phosphorus-containing diacid is phosphorylsuccinic acid, and the sulfonic diol is at least one of 2,3-dihydroxypropane-1-sulfonic acid, 1,3-dihydroxypropane-2-yl-4-methylbenzenesulfonate, 1,5-dihydroxypentane-1,5-disulfonic acid disodium, and 1,4-dihydroxy-2-butane sodium sulfonate.
6. The flame retardant and wear resistant fabric according to claim 3, characterized in that: The catalyst is a titanium-based catalyst or an antimony-based catalyst.
7. The flame retardant and wear resistant fabric according to claim 1, characterized in that: The water-based acrylic resin is selected as 6014 water-based acrylic resin produced by Runchang Chemical.
8. The flame retardant and wear resistant fabric according to claim 1, characterized in that: The solvent is a 50 wt% ethanol aqueous solution.
9. The flame retardant and wear resistant fabric according to claim 1, characterized in that: The coupling agent is at least one of KH171, KH151, and ethylenetri[(1-methylvinyl)oxy]silane.